Hubungan Pengetahuan Ibu Dan Status Gizi dengan Risiko Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Johan Pahlawan Kabupaten Aceh Barat Tahun 2026 - Fatima Zuhra; Lili Eky Nursia; T. Alamsyah; Kiswanto Kiswanto; Pesona Dessritina (KOLONI, 2026)
Diarrhea remains a significant public health issue among children under five, with incidence rates fluctuating annually in the working area of Johan Pahlawan Health Center, West Aceh Regency. Maternal knowledge and nutritional status are suspected determinants of diarrhea risk. This study aimed to determine the relationship between maternal knowledge, nutritional status, and the risk of diarrhea among children under five in this area, using an analytical survey design with a cross-sectional approach. The population consisted of all mothers with children aged 12–59 months (3,749 individuals), with a sample of 98 respondents determined using Slovin's formula (90% confidence level) and allocated across 11 villages through proportional random sampling. Data were collected through structured interviews and analyzed using the Chi-Square test (α=0.05). Results showed that out of 98 children, 83 (84.7%) were at risk of diarrhea. A significant relationship was found between the risk of diarrhea and both maternal knowledge (p=0.000) and height-for-age (TB/U) status (p=0.000), whereas weight-for-age (BB/U) status (p=0.321) and weight-for-height (BB/TB) status (p=0.391) showed no significant relationship. It is concluded that improving maternal knowledge and addressing stunting should be priorities in reducing diarrhea risk among children under five. Health centers are recommended to strengthen continuous maternal education and conduct routine growth monitoring at Posyandu for early detection of stunting and prevention of diarrhea.